Financial Literacy, Risk Tolerance, and Financial Inclusion on Investment Decisions: Investor Behavior Mediation - Rendy Cristianto; Eka Desy Purnama (Journal of Digital Business and Marketing, 2026)
Purpose: This study analyzes the implementation of the 5C+1S Principles in Islamic Financial Institutions, focusing on its effectiveness in providing financing. Methods: This study used a descriptive research method. Data collection techniques included literature review and triangulation, utilizing various data sources to ensure comprehensive analysis. Results: The findings highlight several key points for each of the 5C+1S Principles. The Character principle emphasizes the importance of debtor discipline. The Capacity principle focuses on whether the customer owns a business, while capital concerns the amount of funds used by the debtor in their business. Collateral is the guarantee provided by the debtor, and the Condition of Economy evaluates the debtor's ability to handle future economic situations. The Sharia principle ensures that the customer’s business does not violate Islamic law and complies with the fatwa of the DSN. Conclusions: This study confirms that implementing the 5C+1S Principles is beneficial for Islamic Financial Institutions in ensuring responsible financing and minimizing the risk of bad debt. Limitations: The researcher acknowledges certain limitations of this study, particularly regarding the depth of analysis, as this study only briefly explores the 5C+1S principles in the context of financing. Contributions: The authors hope that this study will be useful and provide insights.